Study of Association of Serum Lipid Levels with Migraine (Journal of Enam Medical College, 2020)
Background: Migraine is associated with increased prevalence of cardiovascular risk factors and vascular biomarkers and migraine with aura is associated with increased risk of ischemic stroke. Lipid abnormality is a risk factor for both cardiovascular and cerebrovascular disease. The vast majority of previous studies evaluated the association between lipid levels and migraine among young and middle aged persons abroad. So far we know, no study has been conducted in Bangladesh regarding association of lipid levels with migraine.Objectives: The present study is aimed to evaluate the association between serum lipid levels in patients with migraine.Materials and Methods: This observational, cross-sectional study was carried out on 100 patients in outpatient departments of Enam Medical College and Hospital, Dhaka and Mymensingh Medical College Hospital, Mymensingh over a period of one year (December 2017 to November 2018). Patients were selected by purposive sampling. Fifty migraine and 50 non-migraine patients were recruited in the study.Results: The serum total cholesterol and LDL-C were significantly higher in migraine than in non-migraine group. HDL-C was below normal and triglyceride was within normal range in both groups. Serum total cholesterol and LDL-C were significantly higher in migraine with aura than migraine without aura. HDL-C level was lower in migraine without aura and was of normal level in migraine with aura, which was statistically significant.Conclusion: Elevated levels of serum total cholesterol and LDL cholesterol were associated with migraine than non-migraine group. Serum total cholesterol and LDL cholesterol were significantly higher in late age of migraine group and migraine with aura.J Enam Med Col 2020; 10(1): 27-32